To simplify the denominator of the expression \( -(-3)^2 \), we start by evaluating \((-3)^2\).
\[ (-3)^2 = 9 \]
Now, substituting this value back in, we have:
\[ -(-3)^2 = -9 \]
Thus, the simplified denominator is:
\[ \boxed{-9} \]
. What is the simplified denominator?
1 answer
To simplify the denominator of the expression \( -(-3)^2 \), we start by evaluating \((-3)^2\).
\[ (-3)^2 = 9 \]
Now, substituting this value back in, we have:
\[ -(-3)^2 = -9 \]
Thus, the simplified denominator is:
\[ \boxed{-9} \]